Canine Ringworm Caused by Trichophyton mentagrophytes - Detection by SYBR-Green real-time PCR - Spanamberg, Andréia; Lupion, Camila; Tomazi , Natália; Ravazzolo, Ana Paula; Fuentes, Beatriz; Ferreiro, Laerte (Acta Scientiae Veterinariae, 2023)
Background: Dermatophytes, fungi of universal distribution, invade semi or fully keratinized structures, such as skin, fur/hair and nails. The various species of dermatophytes are classified into three genera anamorphic: Microsporum, Trichophyton and Epidermophyton. The genus Epidermophyton includes only E. floccosum, that rarely affects animals. The main species responsible for the disease in dogs and cats are Microsporum canis, M. gypseum and Trichophyton mentagrophytes, which were characterized through conventional mycological methodology (microscopic examination with KOH and culture). Molecular methodologies, such as real-time PCR, can contribute to a rapid laboratory diagnosis, helping clinicians to initiate an early antifungal treatment. This case report describes a case of canine dermatophytosis due to Trichophyton mentagrophytes detected from a clinical sample by SYBR-Green real-time PCR. Case: A 8-year-old dog, rescued from the street, was referred to a private veterinary clinic in the city of Canoas, RS, Brazil, presenting generalized lymphadenomegaly, crusted lesions all over the body, generalized alopecia, signs of excoriation and epistaxis. Initially, were administered prednisone [1 mg/kg every 48 h, BID] and cephalexin [30 mg/kg, BID]. Weekly baths with benzoyl peroxide were also given. The therapy was not clinically successful. Wood’s Lamp Test was negative. As a differential diagnosis, PCR for detection of Leishmania was negative. Complete blood count and serum biochemical assay were also performed. For mycological diagnosis, hair specimen was clarified and examined microscopically using 10% potassium hydroxide (KOH) for the visualization of chains of arthroconidia (ectothrix invasion of hair). The infected hair was plated onto MycoselTM Agar, incubated at 28°C for 15 days. Microscopy of hyphae/ conidia and macroscopic colony characteristics (colors and texture) were conducted for the differentiation of the species within the genus Microsporum and Trichophyton. In addition, real-time PCR was applied for direct analysis of the fungal DNA obtained from the hair sample. Microscopic examination was negative. The dermatophyte present in the hair sample was confirmed as Trichophyton mentagrophytes by culture and qPCR (melting-point analysis). The patient was treated with systemic itraconazole [10 mg/kg SID - 90 days]. Twice-weekly application of 2.5 % miconazole and 2% chlorhexidine shampoo until complete cure. Discussion: Dermatophytosis is often listed as self-limiting infection; however, animal dermatophytosis can spread between pets, as well as a zoonotic transmission to humans. The literature on dermatophytosis indicates that Microsporum canis is the predominant etiological agent, followed by M. gypseum. Trichophyon mentagrophytes that appear in a lower percentage of isolation. The culture of hair, even with specific medium containing chloramphenicol and cyclohexamide, may present contaminating fungi, not related to dermatophytosis, which can inhibit or override the growth of dermatophytes. The use of real-time PCR provided a faster and specific diagnosis of dermatophytosis when compared to the conventional mycological methodology for detection and identification of T. mentagrophytes, which takes around 10 to 15 days for culture. It is possible to use this technique as an alternative diagnosis for dermatophytes associated to clinical hair samples of dogs. Keywords: dermatophytosis, dog, pets, qPCR, hair samples, diagnosis, molecular methodology.